2013
DOI: 10.1890/12-1903.1
|View full text |Cite
|
Sign up to set email alerts
|

Local forcings affect lake zooplankton vulnerability and response to climate warming

Abstract: Abstract. While considerable insights on the ecological consequences of climate change have been gained from studies conducted on remote lakes, little has been done on lakes under direct human exposure. Ecosystem vulnerability and responses to climate warming might yet largely depend on the ecological state and thus on local anthropogenic pressures. We tested this hypothesis through a paleolimnological approach on three temperate large lakes submitted to rather similar climate warming but varying intensities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 75 publications
9
83
0
Order By: Relevance
“…Furthermore, a paleolimnological study conducted in Switzerland in three deep lakes covering the past 70-150 years of climate change found that the response of zooplankton to climate change was largely regulated by local changes in nutrient inputs and fisheries [72]. Specifically, the analyses showed that climate had a very limited effect on the cladoceran community in Lake Annecy, the most nutrient limited lake, whereas Lakes Geneva and Bourget with higher nutrient concentrations were more sensitive to climate warming in the past 70-150 years [72].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a paleolimnological study conducted in Switzerland in three deep lakes covering the past 70-150 years of climate change found that the response of zooplankton to climate change was largely regulated by local changes in nutrient inputs and fisheries [72]. Specifically, the analyses showed that climate had a very limited effect on the cladoceran community in Lake Annecy, the most nutrient limited lake, whereas Lakes Geneva and Bourget with higher nutrient concentrations were more sensitive to climate warming in the past 70-150 years [72].…”
Section: Discussionmentioning
confidence: 99%
“…Cladocera remains are therefore considered to be a good proxy for environmental reconstruction (Frey 1986;Sarmaja-Korjonen 2001;Manca et al 2007;Zawisza and Szeroczyńska 2007;Nevalainen et al 2011;Alric et al 2013). They have been widely used to track historical changes in lake nutrient concentrations, either alone or in combination with other paleolimnological proxies (Jeppesen et al 2001;Davidson et al 2007), pH (Paterson 1994;Jeziorski et al 2008), and also to study historical changes in water levels (Korhola et al 2000(Korhola et al , 2005, submerged macrophyte distributions (Davidson et al 2007) and food webs (Finney et al 2000;Jeppesen et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on subfossil Cladocera have been conducted in Alpine lakes, including both mountain lakes (Lotter et al 1997;Bigler et al 2006;Kamenik et al 2007;Nevalainen et al 2011) and peri-alpine deep lakes such as Lakes Constance (Hofmann 1998), Geneva, Bourget, Annecy (Alric et al 2013;Perga et al 2015) and Zurich (Boucherle and Züllig 1983). However, of the large and deep lakes south of the Alps, which together account for over 80% of Italy's surface freshwater, only Lake Maggiore has been analyzed for subfossil Cladocera (Manca et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cladoceran zooplankton play a central role in the food web structure and ecosystem dynamics of lakes (Eggermont & Martens, 2011;Alric et al, 2013). They are significant grazers of the lower trophic levels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many alpine lakes are also fishless, and can have predominantly pelagic primary producers and consumers with the result that pelagic community dynamics are sensitive to external forcing. In these conditions, cladocerans become important as indicator species and for understanding the long-term ecological change of these lakes (Frey, 1986;Alric et al, 2013). Furthermore, the generally good preservation of their remains in lake sediment after death, the associated record of diversity of subfossil cladoceran assemblages, has allowed the reconstruction of long-term environmental forcing in high altitude lakes around the world (Lotter et al, 1997(Lotter et al, , 1998Kamenik et al, 2007;Kattel et al, 2008;Alric & Perga, 2011).…”
Section: Introductionmentioning
confidence: 99%